Formula of inverse show work

label Calculus
account_circle Unassigned
schedule 1 Day
account_balance_wallet $5

F(x) = (4x+3)/(2x-1)

Feb 24th, 2015

F(x) = (4x+3)/(2x-1)  First switch domain and range

x = (4y+3)/(2y-1)    Then solve for y

Cross multiply to get

2xy - x = 4y + 3

2xy - 4y = x + 3

y(2x - 4) = (x + 3)

y = (x + 3)/(2x - 4)

Therefore,

F^-1(x) = (x + 3)/(2x - 4)

Feb 24th, 2015

Did you know? You can earn $20 for every friend you invite to Studypool!
Click here to
Refer a Friend
...
Feb 24th, 2015
...
Feb 24th, 2015
Jun 23rd, 2017
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle
Final Answer

Secure Information

Content will be erased after question is completed.

check_circle
Final Answer